2022
DOI: 10.1111/jpm.12880
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mental health effects among nurses working during the COVID‐19 pandemic: A systematic review

Abstract: Accessible Summary What is Known on the subject? Working on the frontline during the pandemic has had a negative impact on the mental health of health professionals. A significant proportion experienced anxiety, insomnia, posttraumatic stress or depression. What the paper adds to existing knowledge? Analysis and synthesis of the evidence of the impact of the COVID‐19 pandemic on the mental health of nurses based on their work context. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
5
12
0
Order By: Relevance
“…Likewise, in accordance with our previous results on hardiness, a systematic review by García-Vivar et al highlighted the mental health effects on nurses working in different parts of the world during the COVID-19 pandemic [50]. Indeed, the authors claim that nurses, among all healthcare workers, reported the highest levels of psychological distress because of their working conditions, which worsened when they were female and lacked access to PPE [50]. Accordingly, in our study, the group of nurses caring for COVID-19 patients reported significantly higher values for state and trait anxiety levels than those who did not, indicating that the impact of the COVID-19 pandemic played an important role in nurses' anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, in accordance with our previous results on hardiness, a systematic review by García-Vivar et al highlighted the mental health effects on nurses working in different parts of the world during the COVID-19 pandemic [50]. Indeed, the authors claim that nurses, among all healthcare workers, reported the highest levels of psychological distress because of their working conditions, which worsened when they were female and lacked access to PPE [50]. Accordingly, in our study, the group of nurses caring for COVID-19 patients reported significantly higher values for state and trait anxiety levels than those who did not, indicating that the impact of the COVID-19 pandemic played an important role in nurses' anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…37 A meta-analysis incorporating cross-sectional descriptive studies involving 42,222 nurses from 13 countries highlighted ob mental health outcomes, including depression, anxiety, stress, insomnia, and post-traumatic stress disorder, as well as instances of physical and psychological violence in the workplace during the pandemic. 55 Comparing the results of this study with the findings of a systematic review by García-Vivar et al, 56 it appears that out-of-hospital nurses experience a greater prevalence of moderate to severe depression (48.6% vs 38.79%) and anxiety (47.7% vs 29.55%), although this should be verified by statistical tests to indicate whether the differences are indeed significant.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the training impact, the experiences lived through the pandemic have led to signi cant psychological distress, with an increase in anxious-depressive symptoms [21], like what has happened to healthcare professionals in general [22][23][24][25][26][27]. A decrease in sleep hours and quality, and worsening lifestyle habits such as increased consumption of simple sugars, has also been identi ed [28].…”
Section: Introductionmentioning
confidence: 99%